Serum and Ectopic Endometrium from Women with Endometriosis Modulate Macrophage M1/M2 Polarization via the Smad2/Smad3 Pathway. (12th September 2018) - Nie, Mei-Fang; Xie, Qi; Wu, Ya-Hong; He, Hua; Zou, Lu-Jie; She, Xiao-Ling; Wu, Xian-Qing
Abstract : Objective . This study investigated the alterations in macrophage polarization in patients with endometriosis as well as the underlying molecular mechanisms. Methods . Peritoneal washings, serum samples, and endometrial tissues were collected from endometriosis patients and control subjects. Endometrial stromal cells (ESCs) were isolated from endometrial tissue, and conditioned medium was prepared by treating ESCs with or without various concentrations of interleukin- (IL-) 6, estrogen, or progestin. The frequencies of CD86+ and CD163+ cells and expression levels of these markers as well as the cytokines IL-12 and IL-10 were measured in THP-1- (human monocytic leukemia cell) derived macrophages. Results . There was a decrease in the percentage of CD86+ macrophages in the peritoneal wash solution of patients with endometriosis. Ectopic endometrial homogenates could promote M1 to M2 macrophage polarization in response to lipopolysaccharide (LPS), as evidenced by the increased percentage of CD163+ macrophages and increased IL-10 expression as well as a decreased percentage of CD86+ cells and lower IL-12 expression. In contrast, addition of serum from women with endometriosis to THP-1 cells resulted in the polarization of macrophages towards both M1 and M2 phenotypes. Upregulation of Smad2/Smad3 in macrophages upon exposure to eutopic and ectopic endometrial homogenates as well as serum of women with endometriosis was observed, and blockage of Smad2/Smad3 with their inhibitor SB431542 could reverse the macrophage polarization from M1 to M2. Conditioned medium induced by IL-6, but neither estrogen nor progestin, could facilitate M2 polarization. Neutralization of IL-6 diminished macrophage M2 polarization in endometriosis. Conclusion . This study provides detailed evidence supporting alterations in M1 to M2 macrophage polarization that may contribute to the initiation as well as progression of endometriosis.